Ketamine in Prevention and Treatment of Postpartum Depression - Literature Review - Stefaniak, Daria; Chról, Michał; Zielińska, Weronika; Warunek, Aleksandra; Gronowicz, Gabriela; Wanat, Joanna; Dzikowska, Izabela; Homa, Wojciech; Siejka, Agata (Quality in Sport, 2025)
Introduction and purpose: Ketamine, used as an anesthetic and analgesic, has gained considerable attention in recent years in the context of treating various psychiatric disorders, particularly the treatment of drug-resistant depression. A promising application of ketamine appears to be the treatment of postpartum depression. According to the ICD-11 classification, postpartum depression is part of the disorder defined as major depressive disorder and is characterized by the onset of symptoms in the postpartum period, or 12 months after delivery. Conventional treatments for PPD involving both psychotherapy and pharmacotherapy, including non-selective serotonin reuptake inhibitors, may prove inadequate among some patients. ketamine acts on the NMDA receptor and affects the glutamatergic system, showing a significantly rapid antidepressant effect, compared to traditional antidepressants, which may prove crucial in the pharmacotherapy of patients whose response to conventional treatment has proved unsatisfactory. The purpose of this review paper is to present current research on the use of ketamine in the prevention of postpartum depression, including its mechanisms of action, the results of clinical trials to date, and the potential benefits and risks of its use in this specific group of patients. Brief description of the state of knowledge: Both ketamine and esketamine are used in Poland in the pharmacotherapy of drug-resistant depression. In specialized psychiatric centers it is possible to use the drug off-label (ketamine) in the form of intravenous infusion. A therapeutic option approved by the EMA and the Polish Office for Registration of Medicinal Products is esketamine in intranasal form. Currently, there are no clear recommendations in the context of the use of either substance in postpartum depression. Summary: The number of new-onset depressive episodes, including postpartum depression, is growing in the world. The clinical condition of the patient affects many aspects of her life, especially the care of the newborn in the first weeks of the child’s life. New therapeutic options are key to preventing PPD as well as achieving remission. Material and methods: A comprehensive literature review was conducted using PubMed, focusing on articles and research papers published between 2020 and 2025